Neuro Cognitive Improvement during Pregnancy: An Auditory Event Related Potential (ERP) and Neuropsychological Study - Siti Atiyah, Ali; Tahamina, Begum; Faruque, Reza; Wan Rosilawati, Wan Rosli; Wan Nor Azlen, Wan Mohamad (The IT Medical Team, 2018)
Background: Although there is increasing research interest in auditory cognitive function among pregnant women, little is known about auditory cognitive function during the second (mid) and third trimesters of pregnancy. Therefore, we investigated auditory cognitive and behavioral functions during the mid-and third trimesters of pregnancy using event related potentials (ERPs) and neuropsychological tests, respectively. Methods: ERPs were examined using a 128-sensor net, and the PAS, WCST, ZCT, RAVLTIM, RAVLTDR, RAVLTTS were administered as neuropsychological assessment tools. Thirty-nine participants were recruited as a control group (G1, n= 15, non-pregnant), mid trimester (G2, n= 12, 13-26 weeks), and third trimester (G3, n= 12, 26-40 weeks). The auditory oddball paradigm was used during the ERP examination. Subjects silently counted the number of occurrences of a target tone while ignoring the standard tone. Results: The value of mean differences of two stimuli were measured in case of amplitudes of P50, N100 and P300 ERP components. The highest (significantly) amplitudes were found in three, three and two sites in P50, N100 and P300 ERP components, respectively. Pregnant group (G2 and G3 both) evoked the highest (significantly) amplitudes in three, one and two sites in P50, N100 and P300 components, respectively, comparing with the control group (G1). Within pregnant group, G3 possesses the highest (significantly) amplitudes at 2 sites (out of 3) in P50, 1 site (out of 3) in N100 and 1 site (out of 2) in P300 components. The highest amplitude of P300 was observed in G2 comparing with the G3. G2 subjects